Sedative effects of the naturally derived product NSDVT in experimental animals - Luc, Ngo Danh; Hang, Dinh Thi Thu; Hang, Nguyen Thi Thuy; Phu, Le Hong (Tạp chí Nghiên cứu Y học, 2026)
Sleep disturbance is a prominent and debilitating feature of chronic fatigue syndrome, underscoring the need for safe sedative agents. The present study investigated the sedative effects of NSDVT using standardized experimental models in mice. NSDVT was administered orally at 2.5 and 5 g/kg, with diazepam serving as a positive control. Spontaneous locomotor activity, Rotarod test, and hexobarbital-induced sleeping time were assessed. NSDVT significantly reduced both horizontal and vertical locomotor activity compared with baseline and control values. Diazepam produced a more pronounced reduction at 1 hour post-administration, whereas NSDVT, particularly at 5 g/kg, exhibited a stronger effect at 3 hours, indicating a delayed but sustained sedative action. In the rotarod test, both doses of NSDVT and diazepam significantly decreased the latency to fall. Similarly, diazepam exerted a greater effect at 1 hour, while NSDVT at 5 g/kg showed a more marked reduction at 3 hours. In the hexobarbital-induced sleep test, NSDVT did not affect sleep latency but significantly prolonged sleeping time to 113.45% and 150.83% of control values, with statistical significance observed at the higher dose. These findings demonstrate that NSDVT produces a clear sedative effect characterized by central nervous system depression with a delayed onset.